Identification of the SAMHD1 gene in grass carp and its roles in inducing apoptosis and inhibiting GCRV proliferation. Issue 88 (May 2019) - Xu, Xiaowen; Li, Meifeng; Li, Dongming; Jiang, Zeyin; Liu, Changxin; Shi, Xiao; Wu, Chuxin; Chen, Xingxing; Lin, Gang; Hu, Chengyu
Abstract: SAMHD1 is an innate immunity restriction factor that inhibits virus infection through IRF3-mediated antiviral and apoptotic responses. Fish SAMHD1 shares some similar properties with those in mammals. In this study, a SAMHD1 orthologue from grass carp ( Ctenopharyngodon idellus ) was cloned and characterized. The full-length cDNA of CiSAMHD1 is 2792 bp with an ORF of 1884 bp encoding a polypeptide of 627 amino acids. Multiple alignments showed that SAMHD1 is highly conserved among different species. Phylogenetic tree analysis revealed that CiSAMHD1 shared a high degree of homology with Sinocyclocheilus rhinocerous SAMHD1 . Expression analysis indicated that CiSAMHD1 was widely expressed in all tissues tested including the brain, eyes, spleen, gill, intestine, liver, heart and kidney. It was significantly up-regulated in spleen, liver and intestines after treatment with poly I:C. Also, CiSAMHD1 can be induced following stimulation with recombinant IFN in CIK cells. The promoter sequence of CiSAMHD1 was identified to explore the mechanism underlying the transcriptional regulation of CiSAMHD1 . The promoter sequence of CiSAMHD1 (1370 bp) consists of IRF1, IRF3, IRF9 and p65 binding elements. Gel mobility shift assay also showed that IRF1, IRF3, IRF9 and p65 prokaryotic proteins can separately interact with CiSAMHD1 promoter. Dual luciferase assay and q-PCR suggested that the promoter of CiSAMHD1 can be activated by the overexpression of Ci IRF3 and Ci IRF9, but cannot be triggered by Ci IRF1 and Ci p65. In contrast, knockdown of Ci IRF3 or Ci IRF9 inhibits the transcription of CiSAMHD1 . Intriguingly, CCK assay suggested that Ci SAMHD1 decreased cell viability. TUNEL apoptosis assay and Hoechst 33258 staining assay indicated that apoptosis is induced by the overexpression of Ci SAMHD1. Crystal violet staining, detection of two GCRV genes (vp3 and vp5) and viral titration showed that Ci SAMHD1 can suppress the proliferation of grass carp reovirus (GCRV) in CIK cells. Highlights: A SAMHD1 orthologous gene and its promoter region of grass carp were identified and characterized. CiSAMHD1 responds to poly I:C and recombinant IFN stimulation in grass carp tissues and cells. The transcription of CiSAMHD1 is specifically controlled by Ci IRF3 and Ci IRF9. Overexpression of Ci SAMHD1 decreases cell viability and induces apoptosis. Ci SAMHD1 inhibits the proliferation of grass carp reovirus (GCRV) in CIK cells.